Penerapan Big Data dan Kecerdasan Buatan Untuk Keberlanjutan Bisnis: Systematic Literature Review - Rahmadhani Aldi; Muh. Faiq Farhan Najiya; Persada Abdi (PT. Sharia Journal and Education Center, 2026)
This study seeks to gather information on how big data analytics (BDA) and artificial intelligence (AI) are being applied to support business continuity, including their impact on ESG performance, factors that facilitate and hinder adoption, and modifications to how businesses operate. Using a structured literature review (SLR) in accordance with PRISMA 2020 guidelines, this study examines 40 articles from Scopus, Web of Science, IEEE Xplore, and Google Scholar (2021–2026) through a framework that combines the theories of Triple Bottom Line, Resource-Based View, Dynamic Capabilities, Stakeholders, and TOE. The study results show that AI and BDA contribute to environmental aspects (energy efficiency, pollution and waste minimization), social (safe workplaces, flagging human rights issues), and governance (transparency in ESG reporting and fraud detection). These technologies also facilitate a shift to repeatable business patterns and environmentally friendly supply chains. Key factors driving adoption include leadership commitment, digital expertise, investor pressure, and regulatory compliance. Key barriers include high costs, a lack of expertise, and the complexity of integrating systems. This research produces a combined conceptual framework linking AI/BDA adoption to business sustainability, enhancing theoretical insights through a combination of five theories and providing practical guidance for managers and decision-makers.